2018
DOI: 10.3390/ma11020298
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scanning Strategies on Processing of Aluminum Alloy EN AW 2618 Using Selective Laser Melting

Abstract: This paper deals with various selective laser melting (SLM) processing strategies for aluminum 2618 powder in order to get material densities and properties close to conventionally-produced, high-strength 2618 alloy. To evaluate the influence of laser scanning strategies on the resulting porosity and mechanical properties a row of experiments was done. Three types of samples were used: single-track welds, bulk samples and samples for tensile testing. Single-track welds were used to find the appropriate process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 24 publications
1
40
1
2
Order By: Relevance
“…This statement holds for C1 samples manufactured using a range of process parameters ( Figure 3). In a study by Koutney et al [42], Al alloy cubes with varying edge lengths were manufactured. The study reported that the porosity in the top plane of the cubes increased from 0.03% to 5.95% on changing the size from 5 to 13 mm, respectively.…”
Section: Influence Of Size On Density Microstructure and Hardness Omentioning
confidence: 99%
See 1 more Smart Citation
“…This statement holds for C1 samples manufactured using a range of process parameters ( Figure 3). In a study by Koutney et al [42], Al alloy cubes with varying edge lengths were manufactured. The study reported that the porosity in the top plane of the cubes increased from 0.03% to 5.95% on changing the size from 5 to 13 mm, respectively.…”
Section: Influence Of Size On Density Microstructure and Hardness Omentioning
confidence: 99%
“…There have been a few studies that indicate how the overall microscopic and macroscopic quality of SLM parts can be size-dependent [42][43][44][45]. However, the current literature lacks a systematic study which reports on the influence of the size of a sample on the porosity and microstructure of as-built Ti-6Al-4V samples.…”
Section: Introductionmentioning
confidence: 99%
“…The layers were scanned using Chessboard strategy with island size of 5×5 mm, that involves the splitting of entire area into numerous local areas combined with a different scanning order [11]. This SLM strategy is considered beneficial to eliminate residual stresses and overheating of local areas.…”
Section: Slm Processmentioning
confidence: 99%
“…One the other hand, Ali et al [20] reported that the 90°alternating strategy to result in the lowest amount of residual stresses of five investigated strategies. Apart from residual stresses, scanning strategies have also been shown to influence the relative density [21,22].…”
Section: Introductionmentioning
confidence: 99%